Dominant influence of an HLA-B27 restricted CD8+ T cell response in mediating HCV clearance and evolution. - Neumann-Haefelin, C; McKiernan, S; Ward, S; Viazov, S; Spangenberg, H; Killinger, T; Baumert, T; Nazarova, N; Sheridan, I; Pybus, O; von Weizsäcker, F; Roggendorf, M; et al. (2006)
Virus-specific CD8+ T cell responses play an important role in the natural course of infection; however, the impact of certain CD8+ T cell responses in determining clinical outcome has not been fully defined. A well-defined cohort of women inoculated with HCV from a single source showed that HLA-B27 has a strong association with spontaneous clearance. The immunological basis for this association is unknown. However, the finding is especially significant because HLA-B27 has also been shown to have a protective role in HIV infection. We report the identification of an HLA-B27 restricted hepatitis C virus (HCV)-specific CD8+ T cell epitope that is recognized in the majority of recovered HLA-B27 positive women. In chronically HCV-infected individuals, analysis of the corresponding viral sequence showed a strong association between sequence variations within this epitope and expression of HLA-B27, indicating allele-specific selection pressure at the population level. Functional analysis in 3 chronically HCV-infected patients showed that the emerging variant viral epitopes represent escape mutations. In conclusion, our results suggest a dominant role of HLA-B27 in mediating spontaneous viral clearance as well as viral evolution in HCV infection and mechanistically link both associations to a dominant novel CD8+ T cell epitope. These results support the central role of virus-specific CD8+ T cells and the genetically determined restriction of the virus-specific T cell repertoire in HCV infection.